Progress and challenges in the promotion and public-institutional management of agricultural waste in Costa Rica - Suárez-Espinoza, Kerlyn (2022)
The Costa Rican agricultural sector, like all economic and human activities, puts pressure on ecosystems; in agriculture about 50% of farms do not use any type of treatment, and the sector is positioned among those that generate more CO2 emissions. The aim of this research is analyzing the progress and challenges of promotion and public-institutional management of agricultural waste in Costa Rica. The approach used is qualitative and seeks to describe the problem in the Costa Rican territory and to make a review of the literature and theoretical approaches. As main results, the agricultural sector has reduced profitability in the last years, in addition is mostly based on a linear production model, which is concentrated in rural regions. While there are efforts in some products and from the institutionalism, these remain punctual and sometimes without considering the reality of the sector. The research leads to the conclusion that the circular economy plays a fundamental role in the modification of agricultural processes through the incorporation of residues in the production system, within the most suitable opportunities to reduce waste and, in addition, generate added value is found in the food and medical industry, agrofertilizers, and the generation of biodegradable packaging. Finally, it is necessary that policies along this line have a clear line of action of the actors that incorporate them, as well as comprehensive policies that allow the dissemination of information and the incorporation of local and non-governmental actors, as a strategy to promote more efficient management of agricultural waste.